2018
DOI: 10.24093/awej/th.204
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Syntactic Errors among Saudi EFL Learners

Abstract: This study aims to identify and classify syntactic errors made by EFL Saudi secondary students and the causes behind these errors through written form. The study includes 15 female students of the third secondary grade enrolled in Third Secondary School for Females in Al-Quway'iyah. The data were collected from a diagnostic writing test requiring the students to write a composition about one of three topics. The students' errors were classified into 15 different categories and analyzed using the Error Analysis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Journal and Alqhtani (2018) reviewed and analyzed syntactic errors of Saudi EFL students and determined that Saudi students' errors can be classified into seven syntactic subcategories: sentence structure, adverbial clauses, relative clauses, conjunctions, articles, verbs, and prepositions. Alqhtani (2018) also conducted another study in 2018 that reinforced their previous study. The study showed that Arab EFL students' writing errors are syntactical, particularly prepositions.…”
Section: Factors Causing Low Achievement Levels For L2 Students In Samentioning
confidence: 75%
“…Journal and Alqhtani (2018) reviewed and analyzed syntactic errors of Saudi EFL students and determined that Saudi students' errors can be classified into seven syntactic subcategories: sentence structure, adverbial clauses, relative clauses, conjunctions, articles, verbs, and prepositions. Alqhtani (2018) also conducted another study in 2018 that reinforced their previous study. The study showed that Arab EFL students' writing errors are syntactical, particularly prepositions.…”
Section: Factors Causing Low Achievement Levels For L2 Students In Samentioning
confidence: 75%